Densification mechanisms during solid biofuels production made of sawdust, coal and cocoa husks by pressing (2014)
Abstract. Solid biofuels have become a valuable alternative for cleaner energy generation. This work aimed to identify the feasibility of using mixtures between coal, sawdust and cocoa husks for manufacturing pellets and the effect of particle size on their mechanical properties. Moreover, advanced characterization techniques such as Light and Fluorescence microscopy were used for identifying changes on the densification mechanisms due to the variation of raw materials. Cocoa husks exhibited a similar performance as sawdust for binding coal particles; compression ratio and final density of pellets made with sawdust-coal were near to values obtained with cocoa-coal pellets. Optical and fluorescence microscopy showed that coal particles crushed during the process as a result of the fragmentation stage included in the densification mechanisms; the images also reveals the incidence of lignin and protein content in the agglomeration process. The coal particles were brittle; therefore, it was necessary to add either sawdust or cocoa to increase the resilience, strength and durability of the final solids. Identification of the mechanisms taking place during densification is of great importance in order to establish the optimal conditions for producing biomass or coal-biomass pellets. The production of biomass or biomass-coal pellets might create alternatives for developing new renewable energy industries in Colombia.